Investigating the Impact of Multimedia-aided Coherence Teaching on the Quality of EFL Writing in Sulaymani City - جاجي, لؤي سلمان; Jawad, Hoshang Faruq (Sulaimani Journal for Humanities, 2020)
The present study is an extract from an MA dissertation. The study aimed to investigate the impact of teaching coherence elements explicitly based on Lee’s (2002) model, and the effect of teaching coherence elements integrated with videos as a stimulus tool on the quality of participants’ writing. The study followed quantitative method research design utilising textual and statistical analysis of students’ writings. 90 writing papers taken from 45 EFL students who studied English for general purposes in three language centres in Sulaymaniyah city, Kurdistan Region, Iraq were involved in the study. The main study findings showed that teaching coherence explicitly and teaching coherence integrated with videos as a stimulus tool significantly improve the quality of the students’ writing compared to teaching writing via ELT textbooks taught in those EFL courses. The findings also showed that the two proposed ways of teaching coherence helped participants to have better performance in developing their ideas, organising their paragraphs, establishing more logical relations between sentences, using different cohesive devices judiciously to show relations between ideas and indicating their opinions explicitly in their writings. Adopting the suggested approaches of teaching coherence in this study may positively improve students’ writing in English language courses for general purposes. The findings of the study may also help writing EFL curricula designers change their approaches to writing by integrating coherence elements and multimedia-based instructional tasks and activities into ELT textbooks and equip EFL teachers with a range of writing strategies that can be used in EFL classrooms.
Keywords: EFL Writing Strategies; Coherence; Cohesion; Multimedia; Videos; ELT Textbooks; Writing Instruction; EFL Teachers